Horizontal planting of ora-pro-nóbis minicuttings: A novel method (Research, Society and Development, 2021)
Ora-pro-nobis (Pereskia aculeata) is a vegetable that is considered an unconventional vegetable. The demand for this kind of food by population has shown an increasing trend in the markets. However, the lack of technical information for the cultivation of this plant is usually scarce and often impedes its expansion as a commercial crop. The objective of this work was to evaluate the effect of horizontal planting of 2 types of ora-pro-nobis minicuttings directly on the bed and at different planting densities as a new propagation method for the implementation of production system. Experiment was carried out on an open-air bed in the Horticulture Sector of the Experimental Farm of Canguiri (Pinhais, PR, Brazil), belonging to UFPR. Treatments used were: 1) 5 cm semi-hardwood planted at 10 cm spacing between planting lines, 2) 5 cm semi-hardwood planted at 20 cm spacing, 3) 10 cm semi-hardwood planted at 10 cm spacing, 4 ) 10 cm semi-hardwood stake planted at 20 cm spacing and 5) 10 cm hardwood stake planted at 10 cm of spacing. At 60 days after planting, the minicuttings were collected, evaluated and the overall results showed that woody minicuttings obtained higher establishment in the bed (66.7%), highest fresh mass (566.1 g m-2), mass dryness (54.0 g m-2) and dry mass content (12.0 %) of sprouts, and better number of sprouts (41,6 sprouts m-2). Minicutting of the ora-pro-nobis by horizontal planting directly on the bed appears as a promising method for crop system for this species.